Intramedullary nailing versus plating fixation for the treatment of midshaft clavicular fractures: A meta-analysis of randomized controlled trials. (April 2023) - Zhao, Jing-Xin; Zhao, Yan-Peng; Mao, Zhi; Yin, Peng-Bin; Hao, Ming; Lyu, Hou-Chen; Cui, Xiang; Zhang, Li-Cheng; Tang, Pei-Fu
Highlights: IM nailing could increase the shoulder function score after one year post-operatively when comparing with plating fixation. The functional advantage of IM nailing mainly came from the subgroup of locked IM nailing. The rates of the infection, overall major complications and revision surgery were significantly higher after plating fixation than IM nailing. The operative time, blood loss and wound length were significantly less in the IM nailing group than the plating group. Abstract: Purpose: This study was to test the hypothesis that intramedullary (IM) nailing fixation of midshaft clavicle fractures could result in better clinical outcomes and lower complications rates than plating fixation. Methods: PubMed, Embase, and the Cochrane Library database were used to search all English language published randomized controlled trials (RCTs) of midshaft clavicle fractures using plating versus IM nailing. The characteristics of the study participants were collected. Outcomes of postoperative shoulder functional measurements, operative data and complications rates were meta-analyzed. Results: Eight hundred and ninety-five patients in ten RCTs and three quasi-RCTs were involved in the meta-analysis. The results of meta-analysis of these studies showed that the functional outcome evaluated by the Constant Shoulder and Disabilities of the Arm, Shoulder and Hand (DASH) scores after accepting IM nailing was significantly better than that of plating fixation at one year post-operatively ( P < 0.01), with the heterogeneity of 43% and 91%, respectively. Sensitivity analyses of the pooled results of Constant and DASH scores displayed that the functional advantage of IM nailing fixation comes from the subgroup of locked IM nailing. Further, regarding the operative statistics, operative time, blood loss and wound length were significantly less in the IM nailing group than the plating group ( P < 0.001). The rates of infection, major complications and complications-related revision surgery were significantly higher in the plating group than the IM nailing group; however, there were no significantly statistical differences in other complications, e.g., nonunion, refracture after hardware removal, implant failure, symptomatic hardware, etc. ( P > 0.05). Conclusion: The observations in this review suggested that IM nailing, especially locked IM nailing, could provide better shoulder functional outcome at one-year follow-up. Moreover, IM nailing fixation could effectively reduce operative time, blood loss, rates of infection, major complications, and revision surgery than plating. Further high-quality clinical trials with large samples and consistent designs are still needed to verify the long-term functional advantage of locked and unlocked IM nailing for midshaft clavicle fractures. Level of evidence: Level II.